Why Do States Seek to Acquire Nuclear Weapons? - Hamdan Hamedan (The Republic of Indonesia Defense University, 2017)
Conventional wisdom maintains that security concerns are the primary motivation for states to seek nuclear weapons. Indeed, history has shown that the predominant decisions to go nuclear (starting from the U.S., the Soviet Union, China, Israel, Pakistan, and to North Korea) appear to be motivated by security concerns. Yet, the fact there have been nuclear-capable states with precarious security concerns that have decided not to seek nuclear weapons serve to challenge the aforementioned conventional wisdom. Moreover, further research and case-by-case study coupled with understanding of the fact that each state in the world has different security condition and challenges show that security concerns are, in reality, not always the primary motivation.